Global half-BPS AdS2 × S 6 solutions in Type IIB - David Corbino (Journal of High Energy Physics, 2019)
Abstract We investigate half-BPS Type IIB supergravity solutions with spacetime geometry AdS2 × S 6 warped over a Riemann surface Σ. The general local solution was obtained in earlier work in terms of two holomorphic functions A ± $$ {\mathcal{A}}_{± } $$ on Σ. In the first part of this paper we seek global solutions corresponding to the near-horizon behavior of (p, q)-string junctions. We identify the type of singularity in A ± $$ {\mathcal{A}}_{± } $$ needed at the boundary of Σ to match the solutions locally onto the classic (p, q)-string solution. We construct solutions with multiple (p, q)-strings, but the existence of geodesically complete solutions remains unsettled. In a second part we construct multi-parameter families of non-compact globally regular and geodesically complete solutions with asymptotic regions and an AdS2 throat which caps off smoothly.